Manajemen Peningkatan Mutu Berbasis Madrasah di Madrasah Ibtidaiyah Negeri 5 Bulukumba - Agustina Agustina; Muhammad Ramli; Siti Syamsudduha (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2020)
This research aims to describe the implementation of madrasah-based quality improvement management at Madrasah Ibtidaiyah Negeri 5 Bulukumba, South Sulawesi. This research is a qualitative study with a phenomenological approach. The data sources in this study were obtained through the headmaster, teachers, education personnel, and the local community around Madrasah Ibtidaiyah Negeri 5 Bulumba. The data collection techniques used are observations, interviews, and documentation. Processing techniques and data analysis through data reduction, data presentation, and verification or withdrawal of conclusions. The results showed that the madrasah-based quality management at Madrasah Ibtidaiyah Negeri 5 Bulukumba was essentially applied through the involvement of various parties to perform activities in the Madrasah, but not yet walked in accordance with the expected. This is characterized by the lack of discipline of the madrasah and still lack of cooperation with parents of students or communities in the implementation of madrasah-based quality management.